Parental immigration and offspring post-traumatic stress disorder: A nationwide population-based register study - Silwal Sanju; Lehti Venla; Chudal Roshan; Suominen Auli; Lien Lars; Sourander Andre (Elsevier, 2022)
Objectives: The aim of this study was to investigate the association between parental immigration status and a diagnosis of post-traumatic stress disorder (PTSD) in their offspring.
Methods: This nested matched case-control study was based on a Finnish national birth cohort for 1987–2010 and cases were diagnosed with PTSD by 2012 from the Care Register for Health Care. We identified 3639 cases and 14,434 controls individually matched for gender, place and date of birth (±30 days). Conditional logistic regression analyses were conducted to examine the association between parental immigration status, parents’ region of birth and time since paternal immigration, and PTSD after controlling for confounding factors.
Results: The likelihood of being diagnosed with PTSD was significantly increased among children with an immigrant father (OR 1.8, 95% CI 1.3 - 2.4) than those with two Finnish parents and one immigrant mother. There was no significant association between having an immigrant mother or two immigrant parents and receiving a diagnosis of PTSD. The likelihood of being diagnosed with PTSD was increased if the children's fathers had migrated less than five years before their birth (OR 1.4, 95% CI 1.03 - 1.9) and if their immigrant fathers had been born in North Africa or the Middle East (OR 2.1, 95% CI 1.4 - 3.3).
Limitations: The sample included a heterogeneous migrant group without information on the reason for migration. The cases were identified from hospital diagnosis that may have only included severe cases.
Conclusion: he increased likelihood of a diagnosis of PTSD underlines the need for psychosocial services among second-generation immigrants.